2018
DOI: 10.1167/iovs.18-25321
|View full text |Cite
|
Sign up to set email alerts
|

No Relation Between the Severity of Corneal Nerve, Epithelial, and Keratocyte Cell Morphology With Measures of Dry Eye Disease in Type 1 Diabetes

Abstract: PURPOSE. Patients with diabetes have a propensity to develop dry eye symptoms (DES), with reduced tear secretion and corneal sensitivity. The underlying pathologic basis of DES was explored in patients with Type 1 diabetes. METHODS. Forty-two patients with Type 1 diabetes mellitus (T1DM) (age: 49.21 6 2.53 years, duration of diabetes: 29.98 6 2.64 years) and 25 control subjects (age: 48.70 6 2.84 years) underwent assessment of DES using a validated dry eye questionnaire, and tear stability and tear production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
4
10
0
Order By: Relevance
“…These results are in agreement with a large part of literature, bringing evidence that nerve trophism plays a key role on the ocular surface homeostasis, and loss of neural network integrity or correct function is a frequent cause of dry eye disease [26], because of reduced corneal sensitivity and lacrimal gland dysfunction with reduced tear production and tear stability [27]. Our population was not selected on the basis of OS findings, and we found out that at baseline patients with abnormal OSDI had significantly lower sensitivity (21 ± 12 mm) than those with normal OSDI (39 ± 18 mm).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with a large part of literature, bringing evidence that nerve trophism plays a key role on the ocular surface homeostasis, and loss of neural network integrity or correct function is a frequent cause of dry eye disease [26], because of reduced corneal sensitivity and lacrimal gland dysfunction with reduced tear production and tear stability [27]. Our population was not selected on the basis of OS findings, and we found out that at baseline patients with abnormal OSDI had significantly lower sensitivity (21 ± 12 mm) than those with normal OSDI (39 ± 18 mm).…”
Section: Discussionsupporting
confidence: 91%
“…These results are in contrast with Lyu et al [28], who suggested that patients with longstanding diabetes may be less symptomatic due to corneal denervation. Another recent paper by Ferdousi et al [27] found out that DED prevalence in 42 patients with type-1 diabetes was not related with corneal nerve structure and density. Probably, these controversial findings reflect the well-known different effects due to type of diabetes [29], populations (DED on patients with diabetes ranges from 17.5% [30] up to 76.5% [31]), and stage of the disease [32].…”
Section: Discussionmentioning
confidence: 93%
“…These results are in agreement with a large part of literature, bringing evidence that nerve trophism plays a key role on the ocular surface homeostasis, and loss of neural network integrity or correct function is a frequent cause of dry eye disease (26), because of reduced corneal sensitivity and lacrimal gland dysfunction with reduced tear production and tear stability (27). Our population was not selected on the basis of OS ndings, and we found out that at baseline patients with abnormal OSDI had signi cantly lower sensitivity (21 ± 12 mm) than those with normal OSDI (39 ± 18 mm).…”
Section: Discussionsupporting
confidence: 91%
“…These results are in contrast with Lyu et al (28), who suggested that patients with longstanding diabetes may be less symptomatic due to corneal denervation. Another recent paper by Ferdousi et al (27) found out that DED prevalence in 42 patients with type-1 diabetes was not related with corneal nerve structure and density. Probably, these controversial ndings re ect the well-known different effects due to type of diabetes (29), populations (DED on patients with diabetes ranges from 17.5% (30) up to 76.5% (31)), and stage of the disease (32).…”
Section: Discussionmentioning
confidence: 93%
“…These results are in contrast with Lyu et al (22), who suggested that patients with longstanding diabetes may be less symptomatic due to corneal denervation. Another recent paper by Ferdousi et al (21) found out that DED prevalence in 42 patients with type-1 diabetes was not related with corneal nerve structure and density. Probably, these controversial findings reflect the well-known different effects due to type of diabetes (23), populations (DED on patients with diabetes ranges from to 17.5% (24) up to 76.5% (25)), and stage of the disease (19).…”
Section: Discussionmentioning
confidence: 93%